Faktor Yang Berhubungan Dengan Pemanfaatan Posyandu Lansia Di Puskesmas Sibagindar Kecamatan Pagindar Kabupaten Pakpak Bharat - Ujima Siburian; Nur’aini Nur’aini; Tri Niswati Utami (Journal of Educational Innovation and Public Health, 2024)
Based on data from World Population Prospects (2020), it is clear that there are 871 million people aged 60 years or more, which consists of 15% of the world's population. The number of people aged 60 years or older is projected to grow by around 56% from 901 million to 1.4 billion. The aim of the research was to determine the factors related to the utilization of posyandu for the elderly at the Sibagindar Community Health Center, Pagindar District, Pakpak Bharat Regency. The research design uses an analytical survey research method using a cross sectional research design. The population in this study was all 716 elderly people. The sample was 88 with stratified random sampling. Data analysis uses univariate, bivariate and multivariate analysis. The results of the study showed that there was a relationship between knowledge p = 0.000, attitude p = 0.00, distance p = 0.000, family support p = 0.000 and support from health workers p = 0.005 with the utilization of posyandu for the elderly in the Sibagindar Health Center Working Area, Pagindar District, Pakpak Bharat Regency, whereas The dominant factor is family support, p = 0.002 < 0.025 and 95% CI = 3.154-214.028 with an OR value = 25.983. The conclusion of this research is that there is a relationship between elderly knowledge, elderly attitudes, distance, family support, support from health workers with the use of elderly posyandu in the Sibagindar Community Health Center Working Area, Pagindar District, Pakpak Bharat Regency. It is recommended that the Sibagindar Community Health Center increase its role in providing training to health workers and be able to promote the use of posbindu for the elderly and it would be better for door to door health workers to provide education on the use of posbindu for the elderly.